Waqf Empowerment as a Source of Funds in Pesantren DDI Al-Ihsan Kanang - Marhani, Marhani; Riskawati, Riskawati; Hadijah, Hadijah (IAIN Parepare, 2020)
This paper examines the application of waqf to the source of funds for the Pesantren DDI Al-Ihsan in Kanang. Objective is to reveal private educational institutions at the Pesantren DDI Al-Ihsan in Kanang which can carry out an important role in the education of Islam in Indonesia. This paper reveals social facts so that a qualitative research field is carried out. This paper shows that graduates from the Pesantren DDI Al-Ihsan in Kanang have succeeded in becoming quality leaders who are no less competitive than graduates from public educational institutions. The success of graduates can be seen through the ability and independence in managing their finances by optimizing the management of the use of waqf funds. Waqf funds are one of the sources of funds at the Pesantren DDI Al-Ihsan in Kanang to meet their needs, such as in terms of construction and other required facilities.